Augmentative releases of the predatory earwig, Euborellia annulipes Lucas (Dermaptera Labiduridae), for the management of the Asian corn borer, Ostrinia furnacalis (Guenee) - Morallo-Rejesus, Belen (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
The effectiveness of the predatory earwig, Euborellia annulipes Lucas, in the management of the Asian corn borer (ACB), Ostrinia furnacalis (Guenee), the most destructive pest of corn in the Philippines, was evaluated in small- and large-scale field experiments. The use of earwigs as biocontrol agent to suppress ACB population on green corn (variety 'Lagkitan' and 'Asukar') and field corn (variety 'IPB-VAR-1') was subjected to different release regimens (3 times for green corn and 2 times for field corn, respectively, at the rate of 1 earwig/m2/release) and supplemented either with detasseling or microbial insecticide. The comparative treatments consisted of earwigs alone (T1), earwigs plus detasseling (T2), earwigs supplemented with microbial insecticide (T3), insecticide applications (farmers' practice) (T4) and an untreated control (T5). ACB damage was monitored 1 wk before and after earwig releases. The yield taken after harvest was converted to ton/ha. The calendared earwig releases (T1, T2 and T3) from the early whorl stage of the corn plant effectively controlled ACB infestation and prevented it from reaching the control action threshold (CAT) much later than the insecticide applications. Among the green corn treatments (small-scale field trials), earwig releases alone resulted in 45% higher yield than the untreated control. The increase in net income in the three corn varieties 'Asukar', 'Lagkitan' and 'IPB VAR-1' based on earwig releases alone (T1) was 21%, 18.45% and 78.55% more, over the farmers' practice of relying solely on insecticide application. For the field corn, all interventions increased the yield; however, the net income was low due to postharvest costs and low market price of shelled corn. Monitoring for the CAT after the last earwig releases and thereafter is recommended for determining the need and right timing of additional releases of the predatory earwigs or other interventions, especially in sweet corn varieties, which were verified to be more susceptible than the field corn variety.